2014
DOI: 10.1021/nn505468v
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Molecular Mechanism of Apoptosis during Photothermal Therapy Using Gold Nanoprisms

Abstract: The photothermal response of plasmonic nanomaterials can be exploited for a number of biomedical applications in diagnostics (biosensing and optoacoustic imaging) and therapy (drug delivery and photothermal therapy). The most common cellular response to photothermal cancer treatment (ablation of solid tumors) using plasmonic nanomaterials is necrosis, a process that releases intracellular constituents into the extracellular milieu producing detrimental inflammatory responses. Here we report the use of laser-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
312
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 351 publications
(330 citation statements)
references
References 58 publications
17
312
1
Order By: Relevance
“…One important factor of the abovementioned unpredictability lies on the arduous control of the retention of nanoparticles inside a specific organelle, or the difficulty to generate a controlled diffusion of the nanostructures across the entire cell. At first glance it may seem that the heat generated can be retained in a single cell compartment at lower intensities or, if the irradiation is increased, it can literally "melt" the biological membranes [2], starting the diffusion of the nanoparticles throughout the cell [15] (Fig. 1).…”
Section: You Cannot Hit What You Cannot See: Understanding Pttmentioning
confidence: 99%
See 3 more Smart Citations
“…One important factor of the abovementioned unpredictability lies on the arduous control of the retention of nanoparticles inside a specific organelle, or the difficulty to generate a controlled diffusion of the nanostructures across the entire cell. At first glance it may seem that the heat generated can be retained in a single cell compartment at lower intensities or, if the irradiation is increased, it can literally "melt" the biological membranes [2], starting the diffusion of the nanoparticles throughout the cell [15] (Fig. 1).…”
Section: You Cannot Hit What You Cannot See: Understanding Pttmentioning
confidence: 99%
“…What is more, the high specificity of some of these nanoplatforms also grants us with a new tool to further understand the function of certain subcellular components and signaling routes, and how they influence the fate of exposed cells during PTT. In a recent publication, Perez-Hernández et al [15] were able to specifically induce the apoptotic cell death pathway following PTT using gold nanoprisms localized inside the lysosomes by studying several of the steps involved in this complex signaling pathway. They concluded that the death of the cells was mainly mediated by the mitochondrial signaling pathway of apoptosis, hypothesizing that its activation might come from the cleavage of Bid, a pro-apoptotic protein, by the enzymes released from the lysosome where the nanoparticles are localized.…”
Section: Light At the End Of The Tunnel: Research Advancesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that different intracellular locations or shapes of NPs regulate the switch between necrosis and apoptosis. 21,22 In this study, we were able to cause cancer cell apoptosis in vitro and in vivo by adjusting the laser exposure time.…”
Section: Introductionmentioning
confidence: 96%